Micro teaching and students' teaching performance - Yuyun Hendrety; Nyayu Lulu Nadya (UICELL, 2017)
This study investigated to what extend micro teaching develops students’ teaching skill. It was a descriptive qualitative research. It used purposive sampling technique involving two lecturers of micro teaching and 66 seventh semester students majoring at English education study program and Indonesian language and literature education study program in the academic year of 2016/2017. Questionnaire with open ended questions were distributed as the technique for collecting data and then the data were analyzed and interpreted to answer the research question. The finding revealed that microteaching had played a significant role in developing students’ teaching skill. It provided students with both conceptual knowledge as well as teaching practice activities which built up their better understanding and confidence needed in preparing themselves before doing teaching practice program